NGHIÊN CỨU THAY ĐỔI NHIỆT ĐỘ BỀ MẶT ĐÔ DƯỚI TÁC ĐỘNG CỦA QUÁ TRÌNH ĐÔ THỊ Ở THÀNH PHỐ HỒ CHÍ MINH BẰNG PHƯƠNG PHÁP VIỄN THÁM - Vân, Trần Thị; Lan, Hoàng Thái; Trung, Lê Văn (Vietnam Journal of Earth Sciences, 2011)
Research on the change of urban surface temperature under impact of urbanization in Hochiminh City by applying remote sensing method Urbanization changes the urban landscape by replacing the green vegetated areas with the impervious surfaces (IS). Much of the solar energy coming to the land surfaces that could have been utilized to evaporate water is instead transformed into sensible heat in the IS. This effectively raises the temperatures of these surfaces and of the overlying atmosphere in urban areas. This paper presents the research on application of remote sensing to detect the IS in reflective spectra and to retrieve the surface temperature of the urban objects in consideration of the surface emissivity factor in the thermal infrared spectra of 10-12.5μm from LANDSAT and ASTER satellite images. The case study is Hochiminh City, one of the biggest cities of Vietnam. The results show that the urban area increased 6.5 times and the mean surface temperature of the urban 19 inner city raised 0.26°C per year in stage 1989-2006. The correlation of the urban temperature change and urbanization factors (IS, vegetation density and open water area) had been examined. It is found that the relationship of the temperature and impervious surface had the strongest correlation.